Antibacterial Activity of Clove-derived Endophytic Bacteria of Niallia nealsonii DCL1 and Bacillus paranthracis DCL3 - Nadya Nabila Qurani; Jepri Agung Priyanto; Rika Indri Astuti (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Pathogenic bacterial infection is still a major health problem that causes death. Endophytic bacteria in medicinal plants have the potential as antibacterial agents. Thus, endophytic bacteria in the medicinal plant, clove (Syzygium aromaticum), allow it to produce the same bioactive compounds as those contained in its host. This study aimed to analyze the antibacterial activity of five endophytic bacterial isolates from clove leaves. Antibacterial activity was evaluated using disc diffusion assay. Based on the results, isolate Niallia nealsonii DCL1 have strong antibacterial activity against Escherichia coli ATCC 8739, while Bacillus paranthracis DCL3 isolate has intermediate antibacterial activity against Pseudomonas aeruginosa ATCC 15442. In addition, extracellular metabolites of these two isolates of DCL1 and DCL3 which harvested at stationary phase showed antibacterial activity against and E. coli ATCC 8739 and P. aeruginosa ATCC 15442. These data indicate that the potential antibacterial compounds from DCL1 and DCL3 are considered extracellular secondary metabolites. Further analysis on the mode of antibacterial action should be carried out for further medical application.